LEGAL AMBIGUITY AND MARKET PERCEPTION OF UNFAIR TERMS IN COMMERCIAL CONTRACTS: EMPIRICAL AND DOCTRINAL REFLECTIONS FROM UZBEKISTAN (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores the problem of legal uncertainty surrounding unfair terms in commercial contracts in Uzbekistan. Although national legislation formally upholds principles of contractual freedom and equality, business practices reveal a persistent imbalance in bargaining power. Based on empirical survey data and doctrinal analysis, the paper identifies common examples of unfair clauses, highlights the absence of clear legal standards for their regulation, and compares Uzbekistan’s framework with European legal models. The findings point to a legal vacuum and emphasize the need for systematic reform, including the codification of fairness criteria and the development of preventive legal mechanisms.
Keywords: Unfair terms, commercial contracts, contractual imbalance, freedom of contract, legal uncertainty, empirical legal study, Uzbekistan, legal reform, consumer protection, bargaining power.